Hubungan Faktor-Faktor Penguasaan Kefahaman Konsep Matematik Dengan Minat Bagi Pelajar Sarjana Muda Pendidikan Teknik Dan Vokasional - Ali , Azita; Harun, Nor Aini (Online Journal for TVET Practitioners, 2017)
The purpose of this study is to identify the level of student interest in mathematics and the mastery of understanding concept among students of the Faculty of Technical and Vocational Education at Universiti Tun Hussein Onn Malaysia. 285 respondents were randomly selected among the student of the Faculty of Technical and Vocational Education which taken Mathematics 1 and Mathematics 2 of first to fouth year which comprising 7 programs in FPTV. The study was conducted using a quantitative approach through questionnaires. Data were analyzed using descriptive and inferential statistics to get percentage, mean, standard deviation (SD) and Pearson correlation. The results mean score of students' interest in mathematics is 4.2074 was at a high level, while the mean score of teaching and learning is at the level of 3.7023 is moderate. The results mean for the concept of formula also 3.6768 are moderate and the results for the environment is also at the level of 4.2846 high. Pearson correlation test result for the relationship between teaching and learning (P&P) and student interest is r = 0.484 and there is a strong positive relationship. Correlation test for the relationship between the formula and the students interest is r = 0.145 and there is a correlation was very weak and the relationship between the environment and the student interest is r = 0.305 and there is a weak positive relationship. Overall, it can be concluded that the mastery conceptual understanding of learning’s method, formula factors and environmental factors affect student’s interest in mathematics.